Panjabi Bolo: Endless Obstacles to Minority Language Survival - Charanjit Kaur; Ashwinder Kaur; Parveenpal Kaur (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2023)
Every social group possesses its own linguistic system (oral and written). In addition to being essential for communication and idea exchange, language also serves as a cultural indicator for a particular ethnic identity. The technological innovations present a number of obstacles, in particular for ethnic minorities, when it pertains to the safeguarding of the authentic form of the language. Malaysian Sikhs, a minority within a minority in the country, are no exception. The Sikh community of Malaysia is an ethnolinguistic and ethnocultural group that seems to be culturally rooted but is experiencing a gradual decline in the use of its historical language. Considering this, this article explores the ongoing difficulties faced by the Sikh community in preserving their mother tongue. This study's findings were derived from in-depth interviews with Panjabi youths conducted via Google Forms and Zoom calls. Three themes emerged from the interview analysis regarding the language challenges faced by Sikh youths. The members’ use of Panjabi was hampered by an unsupportive environment, a lack of parental initiative, and lack of exposure to socio-religious materials. The research led to the conclusion that the Panjabi language could be preserved if parents made an effort to guide their children and emphasised the significance of speaking their mother tongue. The Panjabi language is an important but perilous part of cultural heritage that must be protected for the sake of future generations. Researchers have forecast that the Panjabi language will deteriorate to the point where it will become extinct if proactive measures to preserve the language are not taken.